Topical Ophthalmic Liposomes Dual-Modified with Penetratin and Hyaluronic Acid for the Noninvasive Treatment of Neovascular Age-Related Macular Degeneration - Sun C; Zhang S; Xu N; Liu K; Wei F; Zhang X; Zhang J; Gao S; Yu Y; Ding X (International Journal of Nanomedicine, 2024)
Chen Sun,1,* Shuyue Zhang,1,* Nan Xu,1,* Kun Liu,2 Fang Wei,2 Xiaoqian Zhang,1 Jigang Zhang,1 Shen Gao,3 Yuan Yu,4 Xueying Ding1 1Clinical Research Center, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200080, People’s Republic of China; 2Department of Ophthalmology, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine; Shanghai Key Laboratory of Ocular Fundus Diseases, Shanghai General Hospital, Shanghai Engineering Center for Visual Science and Photomedicine, Shanghai, 200040, People’s Republic of China; 3Department of Pharmacy, Changhai Hospital, Second Military Medical University, Shanghai, 200433, People’s Republic of China; 4Department of Pharmacy, Naval Medical University, Shanghai, 200433, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xueying Ding, Clinical Research Center, Shanghai General Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 200080, People’s Republic of China, Email dingxueying@126.com Yuan Yu, Department of Pharmacy, Naval Medical University, Shanghai, 200433, People’s Republic of China, Email pharmyuu@163.comIntroduction: Since intrinsic ocular barrier limits the intraocular penetration of therapeutic protein through eye drops, repeated intravitreal injections of anti-vascular endothelial growth factor (anti-VEGF) agents are the standard therapy for neovascular age-related macular degeneration (nAMD), which are highly invasive and may cause particular ocular complications, leading to poor patient compliance.Methods: Using Penetratin (Pen) as the ocular penetration enhancer and hyaluronic acid (HA) as the retina-targeting ligand, a dual-modified ophthalmic liposome (Penetratin hyaluronic acid-liposome/Conbercept, PenHA-Lip/Conb) eye drop was designed to non-invasively penetrate the ocular barrier and deliver anti-VEGF therapeutic agents to the targeted intraocular tissue.Results: PenHA-Lip effectively penetrates the ocular barrier and targets the retinal pigment epithelium via corneal and non-corneal pathways. After a single topical administration of conbercept-loaded PenHA-Lip (PenHA-Lip/Conb), the intraocular concentration of conbercept peaked at 18.74 ± 1.09 ng/mL at 4 h, which is 11.55-fold higher than unmodified conbercept. In a laser-induced choroidal neovascularization (CNV) mouse model, PenHA-Lip/Conb eye drops three times daily for seven days inhibited CNV formation and progression without any significant tissue toxicity and achieved an equivalent effect to a single intravitreal conbercept injection.Conclusion: PenHA-Lip efficiently and safely delivered conbercept to the posterior eye segment and may be a promising noninvasive therapeutic option for nAMD. Keywords: ocular drug delivery, dual-modified liposomes, Penetratin, hyaluronic acid, conbercept